2008
DOI: 10.1242/jcs.032003
|View full text |Cite
|
Sign up to set email alerts
|

TRPC1 binds to caveolin-3 and is regulated by Src kinase – role in Duchenne muscular dystrophy

Abstract: Summary TRPC1 binds to caveolin-3 and is regulated by Src kinase -role in Duchenne muscular dystrophy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
138
2
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(151 citation statements)
references
References 72 publications
(112 reference statements)
9
138
2
2
Order By: Relevance
“…However, more recent reports have raised the possibility that the extent of contraction-induced injury may be affected indirectly by the absence of the DGC. Specifically, they demonstrated that, during either development or cycles of degeneration/regeneration, lack of the DGC leads to deleterious outcomes, such as inflammatory signaling (35,36) or abnormal localization/function of caveolae (37), membrane-bound enzyme complexes (38,39), and ion channels (40)(41)(42). These features have the potential to alter calcium influx/handling, the levels of reactive oxygen species, and cellular signaling, thereby exacerbating contraction-induced injury by increasing permeability of the sarcolemma, intensifying reactive oxygen species/calcium-mediated damage, and reducing release of calcium from the sarcoplasmic reticulum calcium (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent reports have raised the possibility that the extent of contraction-induced injury may be affected indirectly by the absence of the DGC. Specifically, they demonstrated that, during either development or cycles of degeneration/regeneration, lack of the DGC leads to deleterious outcomes, such as inflammatory signaling (35,36) or abnormal localization/function of caveolae (37), membrane-bound enzyme complexes (38,39), and ion channels (40)(41)(42). These features have the potential to alter calcium influx/handling, the levels of reactive oxygen species, and cellular signaling, thereby exacerbating contraction-induced injury by increasing permeability of the sarcolemma, intensifying reactive oxygen species/calcium-mediated damage, and reducing release of calcium from the sarcoplasmic reticulum calcium (43).…”
Section: Discussionmentioning
confidence: 99%
“…New observations suggest that cav-3 expression is necessary for transient receptor potential cation channel canonical 1 (TRPC1) localization. TRPC1 and cav-3 are co-localized and co-immunoprecipitated [35]. TRPC1 is a stretch-activated Ca 2+ channel and seems to play a role in Ca 2+ induced membrane damage in mdx/DMD skeletal muscle fibers [36].…”
Section: Discussionmentioning
confidence: 99%
“…TRPC1 has been shown to form the stretch-activated channel (Maroto et al, 2005), although contrary data also exists (Gottlieb et al, 2008). TRPC1, together with its binding partner caveolin-3, accumulates at higher levels in the sarcolemma of the dystrophin-deficient muscle and contributes to abnormal Ca 2+ influx, which is activated by reactive oxygen species and Src kinase (Allen & Whitehead, 2011;Gervasio et al, 2008). Furthermore, mice lacking the scaffolding protein Homer-1, which interacts with TRPC1, exhibit myopathy associated with increased spontaneous cation influx (Stiber et al, 2008b).…”
Section: Trpc Channelsmentioning
confidence: 99%